Sex‐specific impact of major depressive disorder on 12‐year change in glycaemic status: Results from a nationwide cohort study of adults without diabetes in Germany. Issue 3 (26th December 2021) - Nübel, Julia; Truthmann, Julia; Heidemann, Christin; Du, Yong; Paprott, Rebecca; Hapke, Ulfert; Kruse, Johannes; Scheidt‐Nave, Christa; Baumert, Jens
Abstract: Aims: There is evidence for an increased type 2 diabetes (T2D) risk associated with depression, but its role for diabetes prevention remains unclear. This study aimed to add insight by investigating the impact of major depressive disorder (MDD) on prospective glycaemic changes. Methods: The study was based on a cohort of n = 1, 766 adults without diabetes (776 men, 990 women; 18–65 years of age) who participated in the mental health supplement of the German National Health Interview and Examination Survey (GNHIES98‐MHS, 1997–1999) and in a follow‐up survey (DEGS1, 2008–2011). Glycaemic status was defined as normoglycaemia [HbA1c < 39 mmol/mol (<5.7%)], prediabetes [39 ≤ HbA1c < 48 mmol/mol (5.7–6.4%)] and diabetes [HbA1c ≥ 48 mmol/mol (≥ 6.5%), diagnosed diabetes, or antidiabetic medication], and glycaemic changes categorized as 'remission', 'stability' and 'progression'. Baseline MDD was assessed via a modified German version of the WHO Composite International Diagnostic Interview. Multivariable logistic regressions were applied to analyse the association of MDD with glycaemic changes and incident T2D, adjusting for socio‐demographics, lifestyle conditions, chronic diseases, antidepressant use and mental health care. Results: MDD prevalence was 21.4% for women and 8.9% for men. Among women, MDD was associated with a lower chance for remission (RRR 0.43; 95% CI 0.23, 0.82). Among men, MDD was not significantly related to glycaemic changes. MDD had no significant effect on incident T2D (men: OR 1.58; 0.55, 4.52; women: OR 0.76; 0.37, 1.58). Conclusions: Findings of the current study highlight the role of depression in T2D prevention, particularly among women.